2024
DOI: 10.1161/circulationaha.123.065624
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Base Editing of Scn5a Rescues Type 3 Long QT Syndrome in Mice

Man Qi,
Shuhong Ma,
Jingtong Liu
et al.

Abstract: BACKGROUND: Pathogenic variants in SCN5A can result in long QT syndrome type 3, a life-threatening genetic disease. Adenine base editors can convert targeted A T base pairs to G C base pairs, offering a promising tool to correct pathogenic variants. METHODS: We generated a long QT syndrome type 3 mouse model by introducing the T1307M pathogenic variant into the Scn5a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Recent research also applied AAV9 on in vivo base editing of SCN5A and revealed that complete blocking of SCN5A mutant transcripts can be achieved in SCN5A T1307M mouse models using the base editor adenine base editor (ABE). This study presents a new and very promising therapeutic option to eliminate lethal arrhythmias by fundamentally blocking phenotypic changes brought about by the causative genes at the mRNA level [33] .…”
Section: Treatments Of Brugada Syndromementioning
confidence: 99%
“…Recent research also applied AAV9 on in vivo base editing of SCN5A and revealed that complete blocking of SCN5A mutant transcripts can be achieved in SCN5A T1307M mouse models using the base editor adenine base editor (ABE). This study presents a new and very promising therapeutic option to eliminate lethal arrhythmias by fundamentally blocking phenotypic changes brought about by the causative genes at the mRNA level [33] .…”
Section: Treatments Of Brugada Syndromementioning
confidence: 99%